Utilization of acetone-butanol-ethanol-water mixture obtained from biomass fermentation as renewable feedstock for hydrogen production via steam reforming: Thermodynamic and energy analyses. (August 2018) - Kumar, Brajesh; Kumar, Shashi; Sinha, Shishir; Kumar, Surendra
Highlights: ABE mixture as generally obtained during fermentation of biomass utilized. Optimum performance of SR of ABE occurs at 973 K, 1 atm, and FABE  = 12. SR-ABE produces H2 quantity with energy efficiency comparable to SRB and SRB-E. SR-ABE is environmentally friendly as it uses renewable feedstock. SR-ABE eliminates the need of separation of individual components of mixture. Abstract: A thermodynamic equilibrium analysis on steam reforming process to utilize acetone-butanol-ethanol-water mixture obtained from biomass fermentation as biorenewable fuel has been performed to produce clean energy carrier H2 via non-stoichiometric approach namely Gibbs free energy minimization method. The effect of process variables such as temperature (573–1473 K), pressure (1–10 atm), and steam/fuel molar feed ratio ( FABE  = 5.5–12) have been investigated on equilibrium compositions of products, H2, CO, CO2, CH4 and solid carbon. The best suitable conditions for maximization of desired product H2, suppression of CH4, and inhibition of solid carbon are 973 K, 1 atm, steam/fuel molar feed ratio = 12. Under these conditions, the maximum molar production of hydrogen is 8.35 with negligible formation of carbon and methane. Furthermore, the energy requirement per mol of H2 (48.96 kJ), thermal efficiency (69.13%), exergy efficiency (55.09%), exergy destruction (85.36 kJ/mol), and generated entropy (0.29 kJ/mol.K) have been achieved at same operating conditions.